Avaliação do efeito anti-inflamatório da silibinina sobre monócitos de sangue periférico de indivíduos saudáveis, infectados in vitro com cepa virulenta de Paracoccidioides brasiliensis - Castro, Camila Ferreira Bannwart [UNESP] (2009)
Silibinin is the major active component of silymarin (Silybum marianum), a polyphenolic plant flavonoid that has anti-inflammatory, cytoprotective and anticarcinogenic effects. The modulatory effect of silibinin on monocyte function against Paracoccidioides brasiliensis (Pb18) has not yet been demonstrated. The present study investigated whether the effect of silibinin on NF-kB pathways may affects the production of tumor necrosis factor-alpha (TNF-α), interleukin-10 (IL-10), Transforming growth factor beta (TGF-β1), prostaglandin E2 (PGE2) and nitric oxide (NO), as well as the fungicidal activity of human monocytes challenged in vitro with Pb18. Peripheral blood monocytes from healthy individuals were treated with or without 5 uM and 50 uM silibinin and challenged with Pb18 or were stimulated with lipopolissaccharide (LPS). After 18 h of culture TNF-α, IL-10, TGF-β1 and PGE2 were determined by ELISA, while NO release was quantified by the accumulation of nitrite in the supernatants using the standard Griess assay. Fungicidal activity of monocytes against Pb18 was assessed after cell incubation with interferon-gamma, culture with or without silibinin for 18 h and challenge with Pb18 for 4h. NF-kB activation in the cultures was evaluated by flow cytometry and ELISA after monocyte stimulation with Pb18 or LPS for 30 min. Silibinin at 50uM concentration partially inhibited p65NF-kB activation as observed by reduction in the number of cells expressing this factor, that was confirmed by low concentration detection of p65NF-kB in the nucleus. This silibinin effects resulted in suppression of TNF-α, IL-10, TGF-β1 and PGE2 and NO production, but did not affect fungicidal activity of monocytes against Pb18. The modulatory effect of silibinin on the monocytes inflammatory response against P. brasiliensis might be important to establish an efficient and beneficial immune response of the host against the fungus